(untitled) (Altre Modernità, 2025)
David Hellerstein, The Couch, the Clinic, and the Scanner. Stories from Three Revolutionary Eras of the Mind (New York, Columbia University Press, 2023, 272 pp. ISBN 978-0-231-20792-8) by George Tudorie